The Role of ADCY1 in Regulating the Sensitivity of Platinum-Based Chemotherapy in NSCLC - Ting Zou; Jun-Yan Liu; Zhao-Qian Liu; Di Xiao; Juan Chen (MDPI AG, 2024)
Lung cancer has the highest fatality rate among malignant tumors in the world. Finding new biomarkers of drug resistance is of great importance in the prognosis of lung cancer patients. We found that the polymorphisms of Adenylate Cyclase 1 (ADCY1) are significantly associated with platinum-based chemotherapy resistance in lung cancer patients in our previous research. In this study, we wanted to identify the mechanism of ADCY1 affecting platinum resistance. We used an MTT assay to find if the expression of ADCY1 is associated with the sensitivity of cisplatin in A549, H1299, and A549-DDP cells. Then, we performed CCK-8 tests to detect the absorbance of these cells stimulated by ADCY1, which can discover the cell proliferation that is affected by ADCY1. We investigated cell apoptosis and cell cycles regulated by ADCY1 through the flow cytometry assay. RNA sequencing was used to find the downstream genes affected by ADCY1 which may be associated with drug resistance in lung cancer patients. ADCY1 has higher expression in lung cancer cells than in normal cells. ADCY1 can affect cisplatin resistance in lung cancer cells by regulating cell proliferation, cell apoptosis, and the cell cycle. It may control cell apoptosis by regulating the classical apoptosis biomarkers Bax and Bcl2. Our study showed that ADCY1 may be a new biomarker in the prognosis of lung cancer patients. Much work remains to be carried out to clarify the mechanism in this important emerging field.